A Geotechnical Analysis to Assess the Effect of Slow-Moving Landslides on Historic Masonry Churches. Issue 1 (2nd January 2023) - Ferrero, Chiara; Berardi, Riccardo; Calderini, Chiara; Cambiaggi, Ludovica; Vecchiattini, Rita
ABSTRACT: The protection of cultural heritage from water-soil interaction related threats is a crucial challenge for the scientific community. Among the hazards threatening heritage buildings, slow-moving landslides have been recently found to produce significant damage to historic masonry churches. However, assessing the effects of these phenomena is very challenging, as detailed information about slow-moving landslide movements is not generally available. To tackle this problem, geotechnical analyses can be performed, which enable the landslide-induced soil displacement profiles to be predicted. In view of this, this paper investigates the effects of slow-moving landslides on historic masonry churches by performing geotechnical analyses on two case studies located in the Liguria region (Italy). For each case study, limit equilibrium (LE) and finite element (FE) analyses were carried out with reference to representative sections of the slope on which the building was located. Different scenarios of water table levels were also simulated to evaluate a potential evolution of the slope stability conditions towards failure. Finally, the damage level of the building under study was assessed through a damage criterion available in the literature and compared with the severity of the damage observed on site.